Effectiveness of stress reduction therapy to increase psychological well-being of orphanages’ caregivers - Nurul Hartini, Ratih Saraswaty, Endang R. Surjaningrum, (Opción, 2020)
This research aimed to test the effectiveness of Mindfulness-Based Stress Reduction Therapy to improve the psychological well-being of caregivers. The data are analyzed using visual analysisand effectiveness test, inference analysis with applying Wilcoxon test through SPSS 20.0 for windows.The results indicated that there is an increasing trend of the subjects’ psychological well-being scores after being treated. It suggested that mindfulness-based stress reduction significantly improve the caregiver’s psychological well-being. The Wilcoxon test scored 0.043<0.05.It suggests that there are significant gaps between the caregivers’ psychological well-being before and after being treated with Mindfulness-Based Stress Reduction Therapy.